Competition and Strategic Incentives in the Market for Credit Ratings: Empirics of the Financial Crisis of 2007 - Chu, Chenghuan Sean; Rysman, Marc (American Economic Review, 2019)
We study the market for ratings agencies in the commercial mortgage backed securities sector leading up to and including the financial crisis of 2007–2008. Using a structural model adapted from the auctions literature, we characterize the incentives of ratings agencies to distort ratings in favor of issuers. We find an important equilibrium distortion, which decreased after the crisis. We study several counterfactual experiments motivated by recent policymaking in this industry. (JEL D44, G01, G24)